Culture is not always popular : fifteen years of Design observer - Bierut, Michael; Helfand, Jessica (The MIT Press, 2018)
Founded in 2003, 'Design Observer' inscribes its mission on its homepage: Writings about Design and Culture. Since its inception, the site has consistently embraced a broader, more interdisciplinary, and circumspect view of design's value in the world-one not limited by materialism, trends, or the slipperiness of style. Dedicated to the pursuit of originality, imagination, and close cultural analysis, 'Design Observer' quickly became a lively forum for readers in the international design community. Fifteen years, 6,700 articles, 900 authors, and nearly 30,000 comments later, this book is a combination primer, celebration, survey, and salute to a certain moment in online culture. This collection includes reassessments that sharpen the lens or dislocate it; investigations into the power of design idioms; off-topic gems; discussions of design ethics; and experimental writing, new voices, hybrid observations, and other idiosyncratic texts.- Resumé vydavatel
Essays originally published in Design observer.
Includes index.
Keywords: 20.-21. století; design -- 20.-21. století; design -- sociální aspekty -- 20.-21. století; umělecká řemesla -- 20.-21. století; užité umění -- 20.-21. století; design -- 20th-21st centuries; design -- social aspects -- 20th-21st centuries; arts and crafts -- 20th-21st centuries; applied arts -- 20th-21st centuries; elektronické knihy; kolektivní monografie; obrazové publikace; electronic books; collective monographs; pictorial works